Efficiency of somatic cell count and california mastitis test in the diagnosis of subclinical mastitis in terrincha ewes - Mendonça, Álvaro (2012)
This study aimed to compare the efficiency of microbiological test with Californian Mastitis Test and somatic cell count in the diagnosis of Subclinical Mastitis (SM) in Terrincha sheep. Twenty-seven of a flock of about 200 Terrincha ewes (local breed) were studied for a period of 9 weeks (n > 497 samples). Milk samples were aseptically collected from each half udder once a week. At the same time, another sampled was collected from the bulk tank. After being transported to Lab under refrigeration all samples were immediately processed. The tests performed were the total microbial count (PCA), the Californian Mastitis Test (CMT) and the somatic cell count (SCC). After PCA testing, all samples exceeding 500 cfu/ml of milk (10-1 dilution) were considered positive to mastitis. The SCC was performed by a Fossmatic equipment at the Lactogal Lab. CMT was more accurate to predict Negative (87.1%) than Positive (43.1%) samples (Chi-square = 42.5; P≤0.001), meaning that 12.9% half udders were classified as negative being positive and 47.7% half udders were classified as positive being negative. PCA Negative and Positive samples were related to different SCC values (Negative: 277,048.9 ± 571,249.7 vs. Positive: 800,329.5 ± 1,444.970 somatic cells; P≤0.001), allowing to identify the real Positive (infected) half udders in complement to CMT.